In-field harvest loss of mechanically-harvested maize grain and affecting factors in China - Hou, Liangyu; Wang, Keru; Wang, Yizhou; Li, Lulu; Ming, Bo; Xie, Ruizhi; Li, Shaokun (International Journal of Agricultural and Biological Engineering, 2021)
Field harvest loss is a common problem of maize grain mechanical harvesting in China and abroad. From 2012 to 2019, 2987 groups of samples for the quality of mechanical grain harvesting in field were obtained in 21 major maize-producing provinces, cities, and regions of China. The analysis performed in this study showed that the average harvest loss of fallen ears was equivalent to 76.5% of the total harvest loss, indicating that the harvest loss in the mechanical harvesting of maize grain mainly came from the loss of fallen ears. Meanwhile, statistical analysis of the harvest loss in different ranges of grain moisture contents showed that, when the grain moisture content fell below 20%, the harvest loss rate of fallen ears and the total harvest loss rate both increased sharply, and the harvest loss of fallen ears increased faster than the harvest loss of fallen grain with a decreasing grain moisture content. Moreover, the results of multi-point experiments and harvest experiments in different periods showed that, during harvesting time, the harvest loss of fallen ears caused by lodging was the main reason for in-field harvest losses in the mechanical harvesting of maize grain. Apart from the above mentioned, the test results of 35 groups of harvesters for the in-field mechanical harvesting of maize grain showed that the harvester types and their operating parameters were important factors affecting the harvest loss in the mechanical harvesting of maize grain. Therefore, the principal paths to reduce harvest loss in the mechanical harvesting of maize grain are to breed lodging-resistant maize varieties, adopt reasonable planting densities, cultivate healthy plants, develop harvesters with low harvesting loss, intensify the training of operators, and harvest at an appropriate time.Keywords: maize grain, mechanical harvest, harvest losses, affecting factors, fallen ears, fallen grainDOI: 10.25165/j.ijabe.20211401.6036Citation: Hou L Y, Wang K R, Wang Y Z, Li L L, Ming B, Xie R Z. In-field harvest loss of mechanically-harvested maize grain and affecting factors in China. Int J Agric & Biol Eng, 2021; 14(1): 29–37.